An investigation of finite wings with leading edge protuberances - Gan, Christopher De Hao (2017)
The agility of humpback whales in spite of their huge physical size has led to increased attention by biologists as well as researchers. This has been associated to their unique pectoral fins which consist of protrusions along their leading edge. The addition of protuberances to the leading edge of airfoils have been found to enhance aerodynamic performance. Although several theories have been proposed, the underlying mechanism behind the leading edge protuberances is still unknown. In the present study, Particle Image Velocimetry (PIV) was carried out in a water tunnel at a Reynolds number of 2.0 x 10^4 to investigate the cross stream flow around finite wings with leading-edge protuberances. Results obtained confirm that the protuberances lead to the generation of counter-rotating vortex pairs (CVPs), similar to the function of vortex generators. These vortex pairs appear to drift apart from one another, subsequently interacting with adjacent vortices at the troughs and becoming unstable. This is confirmed by the streamline and mean vorticity plots further downstream on the airfoil. Irregular streamline patterns were observed and mean vorticity was found to become incoherent and decrease significantly. It was also discovered that larger protuberance wavelengths create stronger and more distinct vortices.